Infants show early comprehension of basic color words - Forbes, SH; Plunkett, K (American Psychological Association, 2019)
Previous research has highlighted the difficulty that infants have in learning to use color words. Even after acquiring the words themselves, infants are reported to use them incorrectly, or overextend their usage. We tested 146 infants from 5 different age groups on their knowledge of 6 basic color words, red, green, yellow, blue, black, and white, using an intermodal preferential looking task. The results showed that infants show reliable comprehension of color words as early as 19 months of age. No order of acquisition effects were observed. In addition, infants’ behavior in the task was facilitated by the provision of redundant noun information, “Look at the red car,” and even general referential noun phrases, “Look at the red one,” with greater looking to the target than when the color label was not presented in adjective position, “Look, red.” The findings indicate that color words may be learned with greater ease than previously thought, verifying recent parental reports showing similar findings. The findings also suggest that 19 month olds have already developed an expectation that color labels should occur in adjectival position. (PsycINFO Database Record (c) 2019 APA, all rights reserved)